2015
DOI: 10.5539/res.v7n9p83
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Estimation of Multiplier Effect of Investments in Development of Infrastructure of Inland Water Transport in the Russian Federation in the Frameworks of Federal Target Programs

Abstract: The offered method for estimation of influence of investments in development of infrastructure of inland waterways provided by Transport strategy of the Russian Federation for the period up to 2030 and Federal target program "The development of transportation system of the Russian Federation (2010-2020s)" on growth of economy of Russia allows estimating the integral multiplier effect. In the study there are methodological approaches and estimations of multiplier effect of investments in realization of number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Having analyzed the advantages and disadvantages of these methods, the authors concluded that the lack of a single integrated method of project evaluation and selection makes it impossible to build an orderly system for project implementation and impedes the uniform development of transport infrastructure, which gives rise to shortcomings in the project management system: there is no single coordination center, as a result of which each region chooses its own policy instruments in the field of transport. The methods used for assessing and selecting projects for the development of transport infrastructure do not take into account their specifics, as well as the issues of goal setting and the specifics of interaction with related industries [17]. Therefore, our proposed method of multi-criteria assessment and selection was developed taking into account the indicated disadvantages.…”
Section: Methodsmentioning
confidence: 99%
“…Having analyzed the advantages and disadvantages of these methods, the authors concluded that the lack of a single integrated method of project evaluation and selection makes it impossible to build an orderly system for project implementation and impedes the uniform development of transport infrastructure, which gives rise to shortcomings in the project management system: there is no single coordination center, as a result of which each region chooses its own policy instruments in the field of transport. The methods used for assessing and selecting projects for the development of transport infrastructure do not take into account their specifics, as well as the issues of goal setting and the specifics of interaction with related industries [17]. Therefore, our proposed method of multi-criteria assessment and selection was developed taking into account the indicated disadvantages.…”
Section: Methodsmentioning
confidence: 99%